2010
DOI: 10.1366/000370210790918364
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Micro-Raman Spectroscopy for in Vitro Detection of Cervical Cancer

Abstract: Near-infrared Raman spectroscopy is a powerful analytical tool for detecting critical differences in biological samples with minimum interference in the Raman spectra from the native fluorescence of the samples. The technique is often suggested as a potential screening tool for cancer. In this article we report in vitro Raman spectra of squamous cells in normal and cancerous cervical human tissue from seven patients, which have good signal-to-noise ratio and which were found to be reproducible. These prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 29 publications
7
93
0
1
Order By: Relevance
“…For instance, the spectra showed decreased glycogen and structural proteins (854 cm −1 ), primarily representing the loss of epithelial cell differentiation during neoplastic progression. 22,32 The increased nuclear content (1095 cm −1 ) indicated the elevated number of epithelial cells in the dysplastic cervix. 22,32,33 The amide I (1654 cm −1 ) and amide III (1253 cm −1 ) bands were also noticeably decreased with dysplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the spectra showed decreased glycogen and structural proteins (854 cm −1 ), primarily representing the loss of epithelial cell differentiation during neoplastic progression. 22,32 The increased nuclear content (1095 cm −1 ) indicated the elevated number of epithelial cells in the dysplastic cervix. 22,32,33 The amide I (1654 cm −1 ) and amide III (1253 cm −1 ) bands were also noticeably decreased with dysplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…1(e) 7,10,[20][21][22] The comprehensive biomolecular basis of Raman spectroscopic diagnosis of cervical dysplasia has been described in detail elsewhere. 7,9,22 The AF spectra show higher intensity for dysplasia; however, the change in AF intensity associated with dysplastic progression was not significant (p ¼…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
“…Therefore, Raman spectroscopy is used for various researches [1][2][3][4][5][6][7][8][9] , suggesting Raman spectroscopic analysis is a powerful and useful tool. There are some advantages to using Raman spectroscopy for analysis of water-rich and multi- The present study demonstrated the micro FT-Raman ability for obtaining the spectra of ghost cells in CCOT and keratinocytes of the gingiva.…”
Section: Original Discussionmentioning
confidence: 99%
“…The loss of differentiation, together with increased proliferation, in precancer results in reduced levels of glycogen, as normal cervical cells accumulate glycogen as they mature. A Raman mapping study using frozen tissue sections showed that Raman spectroscopy could distinguish normal cervical tissue from invasive cervical cancer tissue based mainly on collagen bands and CH stretching bands [41].Tan et al [42] used Raman spectral mapping and hierarchical cluster analysis (HCA) to differentiate between normal squamous epithelium and CIN2 in FFPP tissue sections and it was shown that the Raman spectra associated with the CIN2 lesion clustered predominantly with those of the basal epithelial cells of the normal squamous epithelium, suggesting that the cells of these regions share common biochemical profiles. Spectral features responsible for their differentiation were associated with the amide I and amide III bands.…”
Section: Raman Spectroscopy For Histopathologymentioning
confidence: 99%